Management of patients with ST-elevation myocardial infarction : ACC/AHA pocket gudeline : based on the ACC/AHA guidelines for the management of patients with ST-elevation myocardial infarction - Antman, Elliott M.; Anbe, Daniel T.; Armstrong, Paul Wayne; Bates, Eric R.; Green, Lee A.; Hand, Mary; Hochman, Judith S.; Krumholz, Harlan M.; Kushner, Frederick G.; Lamas, Gervasio A.; Mullany, Charles J.; Pearle, David L.; et al. (s.n., 2004)
This pocket guide provides rapid prompts for appropriate patient management, which is outlined in much greater detail in the full-text guidelines. It is not intended as a replacement for understanding the caveats and rationales that are stated carefully in the full-text guidelines. Users should consult the full-text document for more information. The purpose of these guidelines is to focus on the numerous advances in the diagnosis and management of patients with ST-elevation myocardial infarction (STEMI) since 1999. It is recognized that there are areas of overlap among these guidelines on patients with STEMI, the guidelines on patients with unstable angina/non-STEMI, and other guidelines.